Hippocampal modifications partially mediates the boosted effects of seizure induction on ASD-related behaviors in maternally separated mice, while HMGB1 and MeCP2 mRNA levels remained unchanged - Amir Hossein Mousavi; Shima Balali-Dehkordi; Mohammad Rahimi-Madiseh; Elham Zarean; Hossein Amini-Khoei (Journal of Molecular Histology, 2026)

The Protective Effects of Chlorogenic Acid in Mitigating Gut–Brain Barrier Dysfunction and Autism-Like Symptoms Caused by Early-Life Stress in Mice: A Behavioral, Histopathological, and Molecular Study - Sahreh Shabani; Mehrdad Shahrani; Abbas-Ali Mosayebian; Maryam Anjomshoa; Elham Bijad; Elham Asadi-Farsani; Hossien Amini-Khoei; Sadegh Moradi-Vastegani (Molecular Neurobiology, 2026)

Synergistic Efficacy of Lactobacillus plantarum Supernatant-Preconditioned BM-MSCs in Alleviating Depression, Anxiety-Like Behavior, and Memory Impairment in a Rat Stress Model by Suppressing the NF-κB Pathway - Mohammad Amini; Elahe Motevaseli; Maryam Zahmatkesh; Zahra Yousefi; Elham Esmaeil-Jamaat; Gholamreza Hassanzadeh; Tahmineh Mokhtari (Molecular Neurobiology, 2026)

Differential Transcript Expression and Alternative RNA Splicing Patterns to Differentiate Focal vs. Generalized-Onset Seizures - Rashi Verma; Katie L. Bullinger; Andrea Pearson; Monica Dhakar; Emine Guven; Elham Amini; Roger P. Simon; Robert Meller (Molecular Neurobiology, 2025)
Retrospective diagnosis of a seizure type is pivotal for effective management and treatment of epilepsy. Previously, we demonstrated that RNA signatures could discriminate between non-epileptic spells and epileptic seizures. Here, we investigate the utility of alternative RNA splicing to distinguish generalized versus focal epileptic seizures. Blood samples were collected at baseline, 4–6 h post-seizure, and at discharge from 27 patients undergoing video-electroencephalogram (vEEG) monitoring at the Emory University Hospital. Epileptologists determined seizure classification through vEEG data review. RNA was extracted, sequenced, and analyzed for RNA expression and transcript usage. Classification models were generated to distinguish between patients who had a focal or generalized seizure. The study shows transcriptomic profile changes following EEG-verified focal and generalized seizures. Compared to baseline, focal seizure exhibits limited changes in transcriptomic expression 4–6 h post-seizure and discharge samples. In contrast, generalized seizures demonstrated a broader transcript response, with 74 differentially expressed transcripts at 4–6 h and 70 at discharge. The changes were also evident across different time points between focal and generalized seizure. The study for the first time described the landscape of isoform switching in seizure type. Notably, significant isoform switching without differences in gene expression was observed. We identified 2689 isoform switches linked to 1249 genes among which 742 genes were sensitive to nonsense-mediated mRNA decay (NMD). Significant switches were observed in genes such as CORO1C, ZBTB44, SNHG1, and RPS17. Notably, we also observed novel isoforms, including CD300 (MSTRG.26116.1), RNF216 (MSTRG.52862.7), and RN7SL1 (MSTRG.17010.3) which exhibited significant switching, revealing potential new regulators of gene expression. Differentially expressed transcripts were utilized as classifiers for machine learning (ML) modeling using random forest (rf) and radial support vector machine (rSVM) algorithms, achieving ~ 83% accuracy in classifying generalized seizures, and multivariate adaptive regression splines (mars) algorithm achieving 100% accuracy in identifying focal seizure events. Our findings of blood transcript expression changes, including isoform switch analysis, underscore the potential of blood-based transcriptome analysis for retrospectively distinguishing seizure types and identifying biomarkers for epilepsy management.

Inhibition of TLR4, NF-κB, and INOS pathways mediates ameliorative effect of syringic acid in experimental ulcerative colitis in rats - Maryam Ghasemi-Dehnoo; Hossein Amini-Khoei; Zahra Lorigooini; Maryam AnjomShoa; Elham Bijad; Mahmoud Rafieian-Kopaei (Inflammopharmacology, 2024)

Identification of time-varying system and energy-based optimization of adaptive control in seismically excited structure - Elham Aghabarari; Fereidoun Amini; Pedram Ghaderi (Earthquake Engineering and Engineering Vibration, 2024)

Central and peripheral lung deposition of fluticasone propionate dry powder inhaler formulations in humans characterized by population pharmacokinetics - Stefanie K. Drescher; Yuanyuan Jiao; Mong-Jen Chen; Abhinav Kurumaddali; Jie Shao; Elham Amini; Günther Hochhaus; Jürgen B. Bulitta (Pharmaceutical Research, 2023)

Chronic stress but not acute stress decreases the seizure threshold in PTZ-induced seizure in mice: role of inflammatory response and oxidative stress - Hossein Tahmasebi Dehkordi; Elham Bijad; Elham Saghaei; Mehrdad Shahrani Korrani; Hossein Amini-Khoei (Naunyn-Schmiedeberg's Archives of Pharmacology, 2023)

Paleoenvironmental reconstruction of Saqqez River basin, western Iran: evidence from quaternary deposits and pedogenic carbonates - Khabat Derafshi; Sarem Amini; Mohammad Mehdi Hoseinzadeh; Mary Evans; Elham Fotuhi (Arabian Journal of Geosciences, 2022)

Correction to: Can Pharmacokinetic Studies Assess the Pulmonary Fate of Dry Powder Inhaler Formulations of Fluticasone Propionate? - Günther Hochhaus; Mong-Jen Chen; Abhinav Kurumaddali; Uta Schilling; Yuanyuan Jiao; Stefanie K. Drescher; Elham Amini; Simon M. Berger; Bhargava Kandala; Christine Tabulov; Jie Shao; Brandon Seay; et al. (The AAPS Journal, 2022)

Can Pharmacokinetic Studies Assess the Pulmonary Fate of Dry Powder Inhaler Formulations of Fluticasone Propionate? - Günther Hochhaus; Mong-Jen Chen; Abhinav Kurumaddali; Uta Schilling; Yuanyuan Jiao; Stefanie K. Drescher; Elham Amini; Simon M. Berger; Bhargava Kandala; Christine Tabulov; Jie Shao; Brandon Seay; et al. (The AAPS Journal, 2021)

Evaluation of Nutrient Removal and Biomass Production Through Mixotrophic, Heterotrophic, and Photoautotrophic Cultivation of Chlorella in Nitrate and Ammonium Wastewater - Azadeh Babaei; Mohammad Reza Mehrnia; Jalal Shayegan; Mohammad-Hossein Sarrafzadeh; Elham Amini (International Journal of Environmental Research, 2018)

A Molecular Approach to Epilepsy Management: from Current Therapeutic Methods to Preconditioning Efforts - Elham Amini; Mohsen Rezaei; Norlinah Mohamed Ibrahim; Mojtaba Golpich; Rasoul Ghasemi; Zahurin Mohamed; Azman Ali Raymond; Leila Dargahi; Abolhassan Ahmadiani (Molecular Neurobiology, 2015)

Biotransformation of monoterpenes by immobilized microalgae - Sara Rasoul-Amini; Elham Fotooh-Abadi; Younes Ghasemi (Journal of Applied Phycology, 2011)

Exposure Assessment to Dust and Free Silica for Workers of Sangan Iron Ore Mine in Khaf, Iran - Ali Naghizadeh; Amir Hossein Mahvi; Hossein Jabbari; Elham Derakhshani; Hassan Amini (Bulletin of Environmental Contamination and Toxicology, 2011)